HUBUNGAN ANTARA DUKUNGAN SOSIAL KELUARGA DENGAN SUCCESSFUL AGING PADA LANSIA DI RW 06 DESA BULU KECAMATAN AGROMULYO SALATIGA - Wayan Nandia Sari; Christiana Hari Soetjiningsih (Universitas Negeri Medan, 2020)
This study aims to determine whether or not there is a relationship between family social support and successful aging in the elderly. Successful aging is meant to achieve success in old age with one of the factors being family social support. The subjects of this study were elderly aged between 60-85 years in RW 06 Desa Bulu kec. Argomulyo Salatiga. Data use taken quantitative method with a sample model of saturated and sampling nonprobability sampling. Based on the results of the study the results of correlation coefficient (r) = 0.042; p <0.05 with the influence of social support on successful aging at 4.8% and 95.2% influenced by other factors. The researcher concluded that there was a positive relationship between social support and successful aging in the elderly in RW 06 Desa Bulu Kec. Argomulyo Salatiga. Keywords: Family Social Support; Successful aging